2013
DOI: 10.1002/pmic.201200468
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF-MS-based species identification and typing approaches in medical mycology

Abstract: MALDI-TOF MS-based species identification has found its place in many clinical routine diagnostic laboratories over the past years. Several well-established commercial systems exist and these allow precise analyses not only among bacteria, but also among clinically important yeasts. This methodology shows higher precision than biochemical and microscopic methods at significantly reduced turnaround times. Furthermore, the differentiation of different filamentous fungi including most dermatophytes and zygomycete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
95
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(99 citation statements)
references
References 101 publications
(163 reference statements)
2
95
1
1
Order By: Relevance
“…As already shown with bacteria, MALDI-TOF MS identifies yeasts with rapidity, accuracy, and superiority over conventional phenotypic methods (for review, see references [11][12][13][14][15].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As already shown with bacteria, MALDI-TOF MS identifies yeasts with rapidity, accuracy, and superiority over conventional phenotypic methods (for review, see references [11][12][13][14][15].…”
mentioning
confidence: 99%
“…Nonetheless, Van Herendael et al showed that MALDI-TOF MS analysis using the short extraction method is suitable for the rapid identification of yeast isolates but that its use necessitates the identification threshold to be lower (Ͻ1.7) to account for the lower scores originating from the method (19). Therefore, it was speculated that the highest concordance between acquired spectra and those included in the reference library-in terms of high-confidence (percentage or score) identification-is achievable only if the sample preparation procedure employed for the MALDI-TOF MS system at hand does not differ from that employed to construct the system's reference library (11,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most problems with identification are due to absence, mistakes or incomplete reference spectra as well as differences in sample handling procedures [169]. Hence, reliable identification of organisms by this technique is only possible if the strains used to construct the reference spectral database have been carefully selected and identified by a reliable method such as the sequencing of the ITS region [178].…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…It represents a fresh approach that has the potential to replace conventional fungal identification techniques for a majority of routine isolates encountered in clinical microbiology laboratories [169]. Biomolecules such as nucleic future science group Biomarkers for invasive aspergillosis: the challenges continue Review acids, metabolites, proteins or whole microorganisms are embedded in a crystalline matrix of α-cyano-4-hydroxy-cinnamic acid, vaporized and ionized in a vacuum by a short laser pulse.…”
Section: Mass Spectrometrymentioning
confidence: 99%